Success of vaginal deliveries among women in labor with previous cesarean section: Analysis of 50 cases - Eva Febia; Jimmy Toga Sitorus; Cut Meurah Yeni (Syiah Kuala University, 2011)
This study was purposed to evaluate the success of vaginal deliveries after cesarean (VBAC). This case-series-study was conducted in Zainoel Abidin and Ibu dan Anak Hospital, as referral and teaching Hospitals, Faculty of Medicine Universitas Syiah Kuala, Banda Aceh, from January until October 2011 with descriptive analytic method. The outcomes were the success of VBAC. There were 50 subjects attempted VBAC. From 50 subjects who attempted VBAC, 45 subjects (90%) were succeed in vaginal delivery, 5 subjects (10%) were unsuccessful and had to undergo emergency C-Section. The parameters which were likely to contribute to the success of vaginal delivery in subjects who attempted VBAC were gestational age less than 40 weeks, the progress of cervical dilatation of less than 1 cm in 60 minutes, more ripened cervix on the labor. Parameters such as lower baby’s weight and history of vaginal delivery also result in the success of VBAC. Gestational age, Bishop score, and the progress of cervical dilatation contributed to higher success of VBAC.